Microbial Biosensor for Sensing and Treatment of Intestinal Inflammation - Duolong Zhu; Jeffrey Galley; Jason Pizzini; Elena Musteata; Martin V. Douglas; Walter J. Chazin; Eric P. Skaar; Jeffrey J. Tabor; Robert A. Britton (Advanced Science)
Abstract Synthetic biology has enabled the development of biosensors to detect intestinal inflammation, yet few target the clinically validated biomarker of intestinal inflammation calprotectin with both diagnostic and therapeutic capabilities. Here, an optimized calprotectin biosensor is presented that leverages a zinc uptake regulator (Zur) controlled promoter coupled with a memory circuit to detect and record intestinal inflammation in vivo. The level of biosensor activation strongly correlates with calprotectin levels in the colon of two independent mouse models of colitis. Coupling of the biosensor with the production of the anti‐inflammatory cytokine IL10 allowed for the resolution of chemically induced colitis, demonstrating the ability of the biosensor to sense and respond to disease. This work highlights the utility of developing synthetic organisms for the diagnosis and treatment of intestinal disease using clinically validated biomarkers.